Relationships between the handball-specific complex test, non-specific field tests and the match performance score in elite professional handball players - Hermassi, S.; Chelly, M. S.; Wollny, R.; Hoffmeyer, B.; Fieseler, G.; Schulze, S.; Irlenbusch, L.; Delank, K. S.; Shephard, R. J.; Bartels, T.; Schwesig, R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study assessed the validity of the handball-specific complex test (HBCT) and two non-specific field tests in professional elite handball athletes, using the match performance score (MPS) as the gold standard of performance. METHODS: Thirteen elite male handball players (age: 27.4±4.8 years; premier German league) performed the HBCT, the Yo-Yo Intermittent Recovery (YYIR) test and a repeated shuttle sprint ability (RSA) test at the beginning of pre-season training. The RSA results were evaluated in terms of best time, total time, and fatigue decrement. Heart rates (HR) were assessed at selected times throughout all tests; the recovery HR was measured immediately post-test and 10 minutes later. The match performance score was based on various handball specific parameters (e.g., field goals, assists, steals, blocks, and technical mistakes) as seen during all matches of the immediately subsequent season (2015/2016). RESULTS: The parameters of run 1, run 2, and HR recovery at minutes 6 and 10 of the RSA test all showed a variance of more than 10% (range: 11-15%). However, the variance of scores for the YYIR test was much smaller (range: 1-7%). The resting HR (r2=0.18), HR recovery at minute 10 (r2=0.10), lactate concentration at rest (r2=0.17), recovery of heart rate from 0 to 10 minutes (r2=0.15), and velocity of second throw at first trial (r2=0.37) were the most valid HBCT parameters. CONCLUSIONS: Much effort is necessary to assess MPS and to develop valid tests. Speed and the rate of functional recovery seem the best predictors of competitive performance for elite handball players.